A roadmap for a Metaverse-based digital governance: A case of the Gambia. - Pa Sulay Jobe; Murat Yilmaz; Hüseyin Emre Ilgın (PLoS ONE)
This paper explores the integration of Metaverse technologies into the digital governance framework of The Gambia, in order to identify the sectors where these innovations can be implemented most effectively. Driven by the pursuit of cutting-edge solutions to improve governance, improve public service delivery, and promote citizen engagement, the study uses qualitative analysis methodologies, including interviews with Information Technology (IT) professionals and an examination of government reports. Through the application of NVivo software for data analysis, essential themes and areas suitable for Metaverse applications were uncovered. These include the potential of the Metaverse to fundamentally transform sectors such as education, public service, infrastructure development, urban planning, and cultural heritage tourism. Despite recognizing the capacity of the Metaverse for transformative impact, this research identifies significant obstacles, including technical infrastructure readiness, ethical issues, and the need for policy reform. The findings highlight the need to address these challenges through substantial improvements in digital infrastructure, literacy, ethical guidelines, and policy frameworks. The study calls for a multistakeholder collaboration model, which incorporates government, the private sector, academia, and international bodies, to ensure the successful integration of the Metaverse into the digital governance of The Gambia. Offering comprehensive insights and strategic recommendations, this research underscores the collective effort required of all stakeholders to harness the full potential of the Metaverse, thus facilitating an inclusive and efficient digital governance ecosystem in the Gambia.